(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
MEMS accelerometers are widespread in various applications like inertial sensing applications, indoor robotic navigation, microsurgery, volcanology and also in defense applications. Though various sensing mechanisms are available piezoresistive is still popular due to its simple fabrication and packaging techniques. An incessant development has been made in the growth of piezoresistive accelerometers which has led to various innovations in design, fabrication, packaging and testing. The present thesis focuses to study on MEMS piezoresisitve accelerometer that deals with simulation analysis of quad beam MEMS piezoresistive accelerometer, etch time optimization using a novel corner compensation structure and a detailed discussion on realization of piezoresistive accelerometer with proof mass edge aligned flexures. To determine the device performance two structures quad beam piezoresistive accelerometer with and without gold were analyzed. Damping characteristics were estimated by analyzing different structures of fixed-fixed quad beam piezoresistive accelerometer using a high performance Finite Element processor (Altair Hypermesh) and analysis by means of OptiStrucut module. To analyze the undercutting behavior in fixed-fixed quad beam piezoresistive accelerometer the etch time characteristics were estimated. A study has been done to determine the etching time of different compensation structures using KOH and TMAH etchants using Anisotropic Crystalline Etching Simulator (ACES). To improve the cross axis sensitivity in the device the flexures are made in aligned with the proof mass edges in the present study.